2013
DOI: 10.1371/journal.pone.0077305
|View full text |Cite|
|
Sign up to set email alerts
|

PTCH1 Gene Mutations in Keratocystic Odontogenic Tumors: A Study of 43 Chinese Patients and a Systematic Review

Abstract: BackgroundThe keratocystic odontogenic tumor (KCOT) is a locally aggressive cystic jaw lesion that occurs sporadically or in association with nevoid basal cell carcinoma syndrome (NBCCS). PTCH1, the gene responsible for NBCCS, may play an important role in sporadic KCOTs. In this study, we analyzed and compared the distribution pattern of PTCH1 mutations in patients with sporadic and NBCCS-associated KCOTs.MethodsWe detected PTCH1 mutations in 14 patients with NBCCS-associated KCOTs and 29 patients with sporad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 38 publications
(46 reference statements)
1
61
1
Order By: Relevance
“…As in cases of NBCCS, BCCs thought to arise due to UV exposure in non-NBCCS patients also frequently harbor aberrations in the hedgehog signaling pathway, most frequently with loss of function mutations in PTCH1 (*90 %). Consistent with these observations, nearly 50 % of sporadic KOTs harbor mutations in PTCH1 [18], as well as a subset of sporadic desmoplastic medulloblastomas [19]. The remaining sporadic BCC patients (*10 %) predominantly exhibit gain of function mutations in SMO [20], aberrations that to our knowledge have not yet been described in NBCCS.…”
Section: Molecular Pathogenesismentioning
confidence: 63%
“…As in cases of NBCCS, BCCs thought to arise due to UV exposure in non-NBCCS patients also frequently harbor aberrations in the hedgehog signaling pathway, most frequently with loss of function mutations in PTCH1 (*90 %). Consistent with these observations, nearly 50 % of sporadic KOTs harbor mutations in PTCH1 [18], as well as a subset of sporadic desmoplastic medulloblastomas [19]. The remaining sporadic BCC patients (*10 %) predominantly exhibit gain of function mutations in SMO [20], aberrations that to our knowledge have not yet been described in NBCCS.…”
Section: Molecular Pathogenesismentioning
confidence: 63%
“…Overall, 13 of these PTCH1 mutations have only been reported by our group, four mutations in 1996, and an additional nine mutations in the current study (Chidambaram et al, ; Hahn et al, ; Table ). Of the three remaining PTCH1 mutations, two were previously reported by one additional group and one was reported by two additional groups in HGMD (Fujii et al, ; Guo et al, ; Kato et al, ; Wicking et al, ; Table ). None of these mutations were reported in ClinVar.…”
Section: Resultsmentioning
confidence: 91%
“…The variant p.Ala392Val identified in this study is located in the first ECL domain of PTCH1, which was found to be one of the PTCH1 mutation hotspots (nearly 30%) in Gorlin syndrome (Guo et al., ). According to our molecular modelling results, residues 376–393 of the ECL structure may be significantly altered.…”
Section: Discussionmentioning
confidence: 71%
“…It encodes a 1447‐amino acid transmembrane protein. Mutations of PTCH1 have been shown previously to play a crucial role in the aetiology of Gorlin Syndrome, a rare autosomal dominant disorder (Guo et al., ; Klein, Dykas, & Bale, ). Gorlin syndrome patients are characterized by basal cell carcinomas development since an early age.…”
Section: Discussionmentioning
confidence: 99%